Robot Untuk Mendeteksi Objek dengan Citra Digital dan Notifikasi Short Message Service (SMS) - Toyib, Rozali (LPPM Universitas Dinamika Bangsa, 2023)
The use of the camera can only be used as a monitor which is usually used not equipped with other devices that allow it to hit an object, be it a human or an object and by using a camera is a hardware device that functions to capture images and convert them into digital images that can be read and processed. by a computer using a robot controlled by a smartphone in approaching objects, the camera sensor is useful for detecting colored ball objects. The detected colors consist of Red, Green, Blue, all colors are processed in the microcontroller which functions as the brain of the robot that is made and later the robot will send information in the form of SMS the results of color objects that have been detected. Research results On the camera sensor, the larger the megapixel camera used, the clearer the resulting image will be in the detection process. The time for sending SMS to the destination number is based on the signal quality of the GSM provider used and in developing information, real-time object information can be added. for object detection will be displayed directly by the smartphone connected to the robot.